Studi kinerja pemeliharaan taman di Hotel Melia Bali - Putra, Nengah Satria Prabawa; Kohdrata, Naniek; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap, 2021)
Melia Bali Hotel is one of the luxury hotels under Melia Hotel International Corporation. This hotel becomes one of the favorite destinations for tourists during their stay in Bali. This hotel is also often used as a venue for international events. The Melia Bali Hotel concerns on its garden because it is the highest value of the hotel itself. Therefore, the company ought to preserve the garden to embellish and keep the convenience of the hotel environment. This study aims to examine the garden maintenance performance in Melia Bali Hotel. The method used in this current study is a survey method. Data were collected from questionnaire, interview, observation, and literature. Interview was done with several key persons of the garden. Meanwhile, the questionnaire was delivered to twenty garden employees. According to the result of the study, the Melia Bali uses outsourcing garden maintenance crews. The garden crews working performance in maintaining the Melia Hotel garden shows above technical standard performance uses in this study. The maintenance activities are sweeping, watering, and trimming.